2019
DOI: 10.1161/circulationaha.119.041595
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Dysfunction Is Associated With Myocardial Ischemia and Abnormal Coronary Perfusion During Exercise

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 44 publications
3
125
1
1
Order By: Relevance
“…Investigation of such interaction of obstructive CAD with CMD, by combining a chronic proximal coronary artery stenosis [37,55] with the current model of comorbiditiesinduced CMD, should be the topic of future studies. Such studies should then also include the assessment of flow distribution across the left ventricular wall, as the presence of a coronary artery stenosis causes a regional flow redistribution away from the subendocardium towards the subepicardium [17], whereas comorbidities in the absence of obstructive CAD appear to result in more diffuse and transmurally homogeneous reductions in myocardial blood flow [5,38,50].…”
Section: Methodsological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of such interaction of obstructive CAD with CMD, by combining a chronic proximal coronary artery stenosis [37,55] with the current model of comorbiditiesinduced CMD, should be the topic of future studies. Such studies should then also include the assessment of flow distribution across the left ventricular wall, as the presence of a coronary artery stenosis causes a regional flow redistribution away from the subendocardium towards the subepicardium [17], whereas comorbidities in the absence of obstructive CAD appear to result in more diffuse and transmurally homogeneous reductions in myocardial blood flow [5,38,50].…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…Our finding of a reduction in CFR due to an increase in basal coronary flow, rather than a decrease in maximal flow, is also in good agreement with observations in a variety of patient groups. Thus, in INOCA patients with functional CMD [50], in patients with residual CMD after undergoing percutaneous coronary intervention for obstructive CAD [27], and in patients with diabetes mellitus [46], an increase in basal coronary blood flow per gram of myocardium [50] or increases in basal coronary flow velocity [27,46], as compared to healthy individuals, appears primarily responsible for the reduction in CFR. Moreover, patients with a reduced CFR and an increased basal blood flow demonstrate an increased cardiovascular mortality risk compared to patients with normal basal coronary blood flow and CFR [24].…”
Section: Coronary Microvascular Dysfunctionmentioning
confidence: 99%
“…However, this approach limited because the achievable maximal tachycardia is limited by Wenckebach block, thus affecting CFR determination. Supine exercise testing during coronary angiography with radial or brachial artery access is feasible and can provide clinically relevant information on disease mechanisms ( 95 ). Rahman et al.…”
Section: How To Assess Coronary Vascular Dysfunction In the Catheterimentioning
confidence: 99%
“…Rahman et al. ( 95 ) measured coronary flow velocity and pressure under resting conditions, during intravenous adenosine–mediated hyperemia (140 μg/kg/min), and during bicycle exercise using a supine ergometer in the catheterization laboratory. They found that in patients with angina without obstructive CAD (n = 85), CFR but not microvascular resistance identified patients with maladaptive physiological responses to exercise and subendocardial myocardial ischemia (n = 55; hyperemic subendocardial/subepicardial perfusion ratio <1.0, as revealed by stress perfusion cardiovascular magnetic resonance).…”
Section: How To Assess Coronary Vascular Dysfunction In the Catheterimentioning
confidence: 99%
“…We categorized those patients with microvascular dysfunction to the unclassified ischemic heart disease (IHD) group. In this report, among 154 patients with suspected angina having non-ACh-provoked epicardial coronary spasm ( [4,62,118,[126][127][128][129][130][131][132][133]. The ACh-provocation test can be useful to assess the reactivity (such as spasm) of not only of epicardial coronary arteries but also endothelium-dependent coronary microvessels.…”
Section: Significance Of Microvascular Spasm In Nonobstructive Coronamentioning
confidence: 99%